ARTIFICIAL INTELLIGENCE AS A NEW BATTLEFIELD - Simikić , Siniša (Politeia, 2025)
Henry Kissinger, Eric Schmidt, Daniel Hattenlocker, The Age of Artificial Intelligence and Our Human Future, Club Plus, Belgrade, 2022